(untitled) (Research, Society and Development, 2023)
The sequential production of polyhydroxyalkanoates (PHA) and levan was investigated by microbial fermentation using agro-industrial residues. PHA production was carried out by Cupriavidus necator DSMZ 545 in two steps: a) bacterial growth, using pure (MN) and hydrolyzed (MH) molasses and; b) accumulation of PHA, using standard glycerol (GP) and crude glycerol (GB). The fermented remaining from the C. necator growth stage was separated from the PHA-containing biomass and used in the subsequent production of levan by Bacillus subtilis (natto) Takahashi. The medium containing MH+GP generated a rate of 15 mg of PHA, while the medium based on MH+GB the rate of PHA was almost twice as high (28.4 mg). FTIR spectroscopic analysis of PHA indicated stretching vibrations characteristic for a PHB-like molecule. In turn, the levan produced in this study was precipitated with different volumes of ethanol, generating levans with different molecular weights. The results of the characterization of this fructan by chromatography showed that it was predominantly constituted by fructose units. In addition, the dynamic and kinematic viscosity values for levan were similar in the analyzed concentrations and, therefore, did not provide any clues about the molecular weight of this biopolymer. Finally, the sequential production process of PHA and levan, as a second bioproduct, represents an elegant alternative to reduce the total costs of PHA production.